Political parties and democratic linkage : how parties organize democracy - Dalton, Russell J.; Farrell, David M., 1960-; McAllister, Ian. (Oxford : Oxford University Press, 2011)
This volume examines how political parties ensure the functioning of the democratic process in contemporary societies. Based on unprecedented cross-national data, the authors find that the process of party government is still alive and well in most contemporary democracies.
Parties and representative government -- Parties and election campaigns -- Parties and electoral institutions -- Party mobilization and campaign participation -- Electoral Choice -- Citizens and their policy preferences -- Party images and party linkage -- Voter choice and partisan representation -- Parties in government -- Government formation and democratic representation -- Party policies and policy outputs -- Party evolution.
Includes bibliographical references and index.
Keywords: Political parties; Democracy; Representative government and representation; Political participation